Effects of rotifer and Artemia enrichment in the first feeding and larval morphogenesis of purple mud crab, Scylla tranquebarica larvae - Noorsyarinah Sanudin; Thien, Fui Yin; Katsuyuki Hamasaki; Shigeki Dan; Rossita Shapawi; Gunzo Kawamura; Yong, Annita Seok Kian (Wiley-Blackwell Publishing Ltd, 2022)
The effects of feeding rotifers and Artemia enriched with different types of enrichment in the first feeding and later stages of Scylla tranquebarica larvae were investigated. Two different experiments were conducted each with five enrichment treatments including live and digestible Nannochloropsis sp. and Tetraselmis sp. or commercial product. In Experiment I, the zoea 1 (Z1) larvae were fed with enriched or unenriched rotifers as their first feed until they moulted into the zoea 2 (Z2) stage, while in Experiment II, the zoea 3 (Z3) larvae were fed with enriched or unenriched Artemia until they metamorphosed into megalopa stage. In Experiment I, Z1 fed enriched rotifers showed higher survival, larval stage index (LSI) and carapace length than those in unenriched treatment. However, the highest survival was recorded in larvae fed Nannochloropsis sp. treatment. In Experiment II, Z3 fed Artemia enriched with digestible Tetraselmis sp. exhibited the highest survival and LSI, lowest chela-carapace length ratio and abnormal moulting frequencies. In comparison to live microalgae, digestible treatment resulted in a smaller chela-carapace length ratio with lower abnormal moulting. In conclusion, enrichments tested in this study can be used to enrich rotifers for the first feeding of Z1, while later stage (Z3 onwards) fed Artemia enriched with digestible Tetraselmis sp. improved survival and decreased the abnormal moulting frequencies of Z5 to megalopa stage.